The Effect of Individual Counseling Self-Control Techniques on Narcissistic Students Using Tik-tok Social Media - Sitorus, Clara Cindy C; Nur Arjani, Nur Arjani (Universitas Negeri Medan, 2023)
This research aims to determine the effect of individual counseling self-control techniques on the narcissism of students who use social media tik-tok. The research method used in this research is a quantitative method. The subjects of this research were 4 students in class The instrument used was the narcissistic personality scale for students using social media Tik-Tok, which consisted of 35 valid and reliable question items. The data analysis technique used in this research is the Wilcoxon analysis technique with Î± = 0.05. The results of this research show that before (pre-test) the individual counseling self-control technique was carried out it was 108.6 and after the individual counseling self-control technique was carried out it was 60.5. Based on the Wilcoxon test results, we get J_count > J_tabel where 5 > 0. So it can be said There is